Profil Aspek Sosial, Aspek Ekonomi, dan Aspek Teknis Subak Lepang Pesedahan Toya Jinah Desa Takmung, Kecamatan Banjarangkan, Kabupaten Klungkung - KUSUMA, PUTU WIRAADI; SUARDI, DEWA PUTU OKA; ASTITI, NI WAYAN SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Subak Lepang is located in Banjarangkan District, Klungkung Regency with an area of 165 hectares. That subak is experiencing water limitations so that the farmers are very difficult to get water. Besides that, the dry season is too long, at night the subak members must close the tertiary channel in order to get higher water volume into the rice field. Based on the case hence purpose of this study to know profile of Subak Lepang viewed from social aspect, economic aspect and technical aspect. This research data obtained through structured interviews and documentation then it analyzed by using descriptive qualitative analysis method. The result of this study shows that profile of Subak Lepang viewed from economic aspect is included in high category (69,78%) and from technical aspect included in high category (70,21%) and social aspect included in medium category (67,07%). On the economic aspect, this is due to the cooperation between subak and cooperatives regarding the distribution of subak fertilizer. Technical aspects shows that the maintenance of irrigation facilities obtain a high indicator because subak members able to maintain and keep the Subak Lepang’s irrigation facility. Social aspect in moderate category due to rare water so that subak members should able to manage water more efficient. Therefore, subak members should together to provide a water reservoir for used irrigation so that during the dry season they not lack of water in the rice field.